Development and studies on a compact electron cyclotron resonance plasma source. (10th March 2016) - Ganguli, A; Tarey, R D; Arora, N; Narayanan, R
Abstract: It is well known that electron cyclotron resonance (ECR) produced plasmas are efficient, high-density plasma sources and have many industrial applications. The concept of a portable compact ECR plasma source (CEPS) would thus become important from an application point of view. This paper gives details of such a CEPS that is both portable and easily mountable on a chamber of any size. It uses a fully integrated microwave line operating at 2.45 GHz, up to 800 W, cw. The required magnetic field is produced by a set of suitably designed NdFeB ring magnets; the device has an overall length of  ≈60 cm and weighs  ≈14 kg including the permanent magnets. The CEPS was attached to a small experimental chamber to judge its efficacy for plasma production. In the pressure range of 0.5–10 mTorr and microwave power of  ≈400–500 W the experiments indicate that the CEPS is capable of producing high-density plasma (≈9  ×  10 11 –10 12 cm −3 ) with bulk electron temperature in the range  ≈2–3 eV. In addition, a warm electron population with density and temperature in the range ≈7  ×  10 8 –10 9 cm −3 and  ≈45–80 eV, respectively has been detected. This warm population plays an important role at high pressures in maintaining the high-density plasma, when plasma flow from the CEPS into the test chamber is strongly affected.